Doctoral Student Perfectionism and Emotional Well-Being. (3rd July 2019) - Moate, Randall M.; Gnilka, Philip B.; West, Erin M.; Rice, Kenneth G.
Abstract: This study examined the association between perfectionism and perceived stress, life satisfaction, positive emotions, and negative emotions among a national sample of 528 doctoral students. Latent profile analysis based on a measure of perfectionism supported a 3-class model (i.e., adaptive perfectionists, nonperfectionists, and maladaptive perfectionists). Adaptive perfectionists had the lowest levels of perceived stress and negative emotions and the highest levels of positive emotions and life satisfaction. Maladaptive perfectionists had the highest levels of perceived stress and negative emotions along with the lowest levels of negative emotions.